2007
DOI: 10.1016/s1472-6483(10)60534-2
|View full text |Cite
|
Sign up to set email alerts
|

Microarray detection of Y chromosome deletions associated with male infertility

Abstract: Array-comparative genomic hybridization (CGH) has emerged as a powerful new molecular tool for the high-resolution analysis of copy-number variation and breakpoint analysis. In this study, array-CGH was used to analyse known Yq deletions associated with male infertility. A microarray platform encompassing probes for chromosomes 13, 14, 21, X and Y was developed in-house and was used to detect different Yq deletion types. The successful application of this array for the detection of Yq deletions involving eithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…There is one publication comparing MLPA‐based Y deletion detection with other methods, but unfortunately only the abstract is available in English (Jiang et al ., ). Finally, microarray technology has also been proposed as an alternative assay, but it does not seem to be very cost‐effective and includes many more markers than necessary (Osborne et al ., ).…”
Section: Alternative Methods For Y Microdeletion Testingmentioning
confidence: 97%
See 1 more Smart Citation
“…There is one publication comparing MLPA‐based Y deletion detection with other methods, but unfortunately only the abstract is available in English (Jiang et al ., ). Finally, microarray technology has also been proposed as an alternative assay, but it does not seem to be very cost‐effective and includes many more markers than necessary (Osborne et al ., ).…”
Section: Alternative Methods For Y Microdeletion Testingmentioning
confidence: 97%
“…Alternative methods partially based on the guidelines protocols have been developed using capillary electrophoresis, real‐time PCR, MLPA and array‐CGH (Osborne et al ., ; Kozina et al ., ; Guo et al ., ; Jiang et al ., ; Segat et al ., ) Using the EAA/EMQN multiplexes, but adding a fluorescent label to the primers, allows detection with capillary electrophoresis. Some laboratories have adapted the proposed protocol accordingly, and validated this in house (LH, personal communication).…”
Section: Alternative Methods For Y Microdeletion Testingmentioning
confidence: 99%
“…Indeed, despite recent developments on microarray-based diagnostic platforms (Osborne et al ., 2007), the PCR amplification of a genomic marker initially identified in the reference AZFc sequence remains the most reliable and cost-effective genetic test for gr/gr deletions (Repping et al ., 2003b). This sequence belongs to haplogroup R, a predominant lineage in European populations (Brion et al ., 2005).…”
Section: Genetic and Phenotypical Aspects Of Partial Azfc Deletionsmentioning
confidence: 99%
“…Array CGH systems can provide highly reliable and accurate diagnoses by the direct use of a gDNA target that can be easily prepared from the peripheral blood of infertile men. A recent study demonstrated that array-CGH may be an alternative to multiplex PCR 19.9 ± 11.7 5.5 ± 3.5 b0.05 for the diagnosis of known Yq deletions and may be useful in identifying previously unknown Y chromosome deletions/polymorphisms associated with defective spermatogenesis (Osborne et al, 2007). The microarray platform used in that study, however, included only probes encompassing regions on chromosome 13, 14, 21, X and Y.…”
Section: Discussionmentioning
confidence: 99%